The Effect of Exercise with Different Intensity and Volume on fibroblast growth factor (FGF-2) Gene Expression in Subcutaneous and Visceral Adipose tissue in Male Rats - Ghamar Mirzaei Amirabadi; Mohammad Reza Asad; Mostafa Rahimi (Shahid Beheshti University, 2019)
Purpose: Obesity is the cause of many diseases and the growth of adipose tissue is related to its vascular changes. Studies show that various exercises can affect vascular adipose tissue regulation. The purpose of the present research was to study the effects of high-intensity interval training (HIIT) and moderate intensity continues training (MICT) on fibroblast growth factor (FGF-2) gene expression in visceral and subcutaneous adipose tissues of male Wistar rats.Methods: In this experimental study, 24 male Wistar rat (Age 8 weeks and weighing 220-250 grams), as the study samples, were divided randomly to basal control, 8 weeks control, HIIT training, and MICT training groups. Exercise training groups practiced on rodent's treadmill 5 days per week, for 8 weeks. In MICT groups, the duration and intensity of training protocol were 15 to 60 minutes and 50-75% of VO2max, respectively. In the HIIT group, rats run 4-8×1 min with 70-100% of VO2max and 1 min active recovery with 50-70% VO2max. Subcutaneous and visceral adipose tissue samples were removed 48 hours after the last training session. Real-Time PCR method used to assess FGF-2 gene expression.Results: Results showed that after 8 weeks of MICT and HIIT training, FGF-2 gene expression in subcutaneous and visceral adipose tissues increased and decreased respectively, although these changes were not statistically significant (P>0.05).Conclusion: According to the results, it seems that despite the lack of significant effect of exercise on FGF-2 gene expression, the different responses of the subcutaneous and visceral fat tissues to exercise activity reflected different angiogenic activity. In general, several different angiogenic factors are involved in this process which needs more study.